Exploring Risk Avoidance Practices Among On-Demand Cybercrime-as-Service Operations. (February 2023) - Holt, Thomas J.; Lee, Jin R.; Smirnova, Olga
Criminologists have recently explored online cybercrime-as-service markets where offenders offer hacking tools and services for a fee. So-called "stresser" or "booter" markets offering distributed reflective denial of service (DRDoS) attacks have been a recent target of international law enforcement action. Few have explored the ways in which these operations continued to function under increased enforcement and sanction. This study attempted to address this gap through a qualitative analysis of online advertisements from 44 booter and stresser operators. The findings revealed operators changed their preferred communications and payment platforms, as well as increased the attack methods available to customers. The implications of this analysis for our understanding of illicit online markets, and the decision-making processes of cybercriminals are discussed in detail.